Novel multi-targeted inhibitors suppress ocular neovascularization by regulating unique gene sets. (August 2019) - Yin, Xiangke; Lin, Xianchai; Ren, Xiangrong; Yu, Bo; Liu, Lixian; Ye, Zhimin; Chen, Qishan; Lee, Chunsik; Lu, Weisi; Yu, Dechao; Li, Xuri
Graphical abstract: Abstract: Neovascular diseases, such as many cancers and ocular disorders, are life threatening and devastating. Although anti-vascular endothelial growth factor A (VEGF-A) therapy is available, many patients are not responsive and drug resistance can develop. To try to overcome these problems, combination therapy targeting VEGF-A and platelet-derived growth factor B (PDGF-B) was tested. However, one obvious drawback was that the other VEGF and PDGF family members were not inhibited and therefore could compensate. Indeed, this was, at least to some extent, demonstrated by the disappointing outcomes. To this end, we designed novel multi-targeted inhibitors that can block most of the VEGF and PDGF family members simultaneously by making a fusion protein containing the ligand-binding domains of vascular endothelial growth factor receptor 1 (VEGFR1), vascular endothelial growth factor receptor 2 (VEGFR2) and platelet-derived growth factor receptor beta (PDGFRβ), which can therefore act as a decoy blocker for most of the VEGF and PDGF family members. Indeed, in cultured cells, the novel inhibitors suppressed the migration and proliferation of both vascular endothelial cells and smooth muscle cells, and abolished VEGFR2 and PDGFRβ activation. Importantly, in a choroidal neovascularization model in vivo, the novel inhibitor inhibited ocular neovascularization more efficiently than the mono-inhibitors against VEGFR or PDGFR alone respectively. Mechanistically, a genome-wide microarray analysis unveiled that the novel inhibitor regulated unique sets of genes that were not regulated by the mono-inhibitors, further demonstrating the functional uniqueness and superiority of the novel inhibitor. Together, we show that the multi-targeted inhibitors that can block VEGFR1, VEGFR2 and PDGFRβ simultaneously suppress pathological angiogenesis more efficiently than monotherapy, and may therefore have promising therapeutic value for the treatment of neovascular diseases.